Estimation of Nutrient Content of Unfermented and Fermented Rice Drinks - Rajendran, Emi Grace Mary Gowshika; Ramesh, V. Gowri (Asian Journal of Biological and Life Sciences)
Background: Fermentation of cooked rice has shown to enhance its nutrient content, palatability, organoleptic characteristics and bioavailability of nutrients. Although fermented rice is known to provide immense health benefits, there is not enough literature validating this claim and no scientific data with respect to changes in the nutrient content. Materials and Methods: This study comprised of an experimental design to estimate the nutrient content in fermented and unfermented cooked rice. Standardized procedures using methods from Association of Official Agricultural Chemists, High-performance Liquid Chromatography, 3, 5-Dinitrosalicyclic Acid, Thin Layer Chromatography and data from FSSAI Manual were used to estimate the nutrient content. Results: In 200 mL of fermented rice drink, macronutrient such as carbohydrate and protein content were found to be 2.4 g, dietary fibre content was 19 g and resistant starch content was 19.73 g. Whereas, in 200 mL of unfermented rice drink, protein content was found to be 1.94 g, dietary fibre content was 2.6 g and resistant starch content was 5.33 g. Total calories were found to be increased after fermentation. Micronutrients such as zinc, selenium, iron, vitamins B2, B3 and B5 also showed an increase after fermentation. Conclusion: Based on this evidence, fermented rice drink can be promoted as a traditional, cost-effective health drink.
Keywords: Fermentation; Health; Nutrients; Nutritional Status; Rice; Rice Drink